Bridging Peace and Interfaith Dialogue through Religion Twenty (R20) Forum in Indonesia 2022 - Hanan, Djayadi; Ridwan, Ridwan; Azaria, Sally; Suci, Perwita (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This study examines the Religion Twenty (R21) Forum in Indonesia as a case of interfaith dialogue for peacebuilding. Interfaith dialogue represents a facet of religious inclusion in international relations that has historically been ignored due to the preponderance of secular foundations in realist traditions. Since 11 September 2001, interfaith dialogue has increasingly served as a framework for addressing global religious challenges, including in Indonesia. This study is concerned with exploring the narrative of R20 regarding the emergence, initiation, activities, continuation and criticism of the R20 Forum. The study adopts a qualitative approach. The main question guiding the study is whether the R20 is succeeding in its peacebuilding mission. To solve this puzzle, the study uses the paradigm of interfaith dialogue for change as an analytical framework. This paper argues that the R20 has succeeded in bringing the paradigm of interfaith dialogue for peacebuilding to the fore. However, the continuation of R20 in the future is still in doubt. However, it offers a broader understanding of interfaith dialogue for peacebuilding in Indonesia, enriching knowledge that can inform public policy improvements within the country and serve as a reference for the advancement of interfaith dialogue globally.